Recurrence of Severe Maternal Morbidity: A Population-based Cohort Analysis of California Women - Bane, Shalmali (Paediatr Perinat Epidemiol, 2020)
BACKGROUND: Severe Maternal Morbidity (SMM) has increased in the United States by 45% in the last decade. While the recurrence of several adverse pregnancy outcomes from one pregnancy to the next has been established, the recurrence risk of SMM is unknown. OBJECTIVE: To determine whether women who have SMM in a first pregnancy are at increased risk of SMM in their second pregnancy, compared to women who did not have SMM in their first pregnancy. METHODS: This is a population-based study using linked vital statistics and hospital discharge records from the Office of Statewide Health Planning and Development in California from 1997 to 2012. The study population had their first two singleton births (live births or stillbirths) in California between 1997 and 2012 (n = 1,180,357). The primary exposure was SMM during the hospitalization at first birth and the primary outcome was SMM during the hospitalization at second birth. Prevalence and risk ratios of SMM at second birth were computed for women who did and did not have SMM at first birth, as well as for certain specific indicators of SMM. RESULTS: Of the 1,180,357 women included in this analysis, 9088 (77 per 10,000 births) experienced SMM at first birth. Among these women, the prevalence of SMM at second birth was 470 per 10,000 births, compared to 68 per 10,000 births among women without SMM at first birth. This corresponded to an unadjusted risk ratio of 6.87 (95% CI 6.23, 7.57), which did not differ substantially when adjusted for factors known to be associated with SMM (6.46 [95% CI 5.86, 7.13]). CONCLUSION: Women experiencing SMM in their first pregnancy were at an approximately 6-fold increased risk of experience SMM in their second pregnancy.